Impact of type 2 Diabetes Mellitus for developing severe health complications in Bangladeshi population - Ahmed, Shabbir; Ahmed, Tasnim; Sharmin, Tarana; Quddus, Sharif Mohammad Ruhul (Asian Journal of Medical and Biological Research, 2017)
Type 2 diabetes mellitus is one of the deadliest disease in Bangladesh as its complications are enormous and life threatening. This study demonstrates the prevalence of the complications of type 2 diabetes among the population of Bangladesh. Data of 1000 subjects admitted into BIRDEM General Hospital from May 2015 to April 2016 were taken into consideration. Significantly, it was found that 89% patients had fasting blood glucose (FBG) level greater than 7 mmol/l and 70.8% patients had glycosylated hemoglobin (HbA1c) level greater than 8%. As a consequence, the total population were affected by diverse health complications including lung, liver, cardiovascular, kidney, brain, oral, eye, thyroid, hearing, skin, and so on. Males and females were suffered from these complications without biasedness. Asian J. Med. Biol. Res. June 2017, 3(2): 152-157